Corrigendum to “Post-bleaching patterns of Acanthaster planci, Culcita schmideliana, and Drupella spp. in coral nurseries and natural reefs, Kaafu Atoll, Maldives” [Journal of Marine Studies, 2025, 2(3), 2301] - Elias Bin Mohamad; Oriana Migliaccio (Journal of Marine Studies, 2025)
Refer to:    Post-bleaching patterns of Acanthaster planci, Culcita schmideliana, and Drupella spp. in coral nurseries and natural reefs, Kaafu Atoll, Maldives. Journal of Marine Studies, 2(3), 2301. https://doi.org/10.29103/joms.v2i3.22084. Elias Bin Mohamad, Oriana Migliaccio